Consumer Decision Journey on Choosing Third Wave Coffee Shop in Bandung - Putranto, Fajar Eka; Hudrasyah, Herry (Journal of Business and Management, 2017)
Abstract.Background: The growth of third wave coffee shop in Bandung increasing the competition among competitor. By understand what consumers prioritize in choosing third wave coffee shop can help the industry to be more sustainable.Methods: Qualitative approach like interview with professional worker, focus group discussion with key informants, and direct observation. Also this research use quantitative approach via questionnaire to find the flow of decision journey. This method was given to the Bandung’s third wave coffee consumer from 15-24 years old.Results: The majority of consumers agree with the variables that are shown in pre-purchase and on purchase phase. Thus, there are exist gap which is knowledge gap.Conclusion:The consumer decision journey helps to map how the consumer path in terms of choosing a third wave coffee shop. Then, after the industry find and understand the path, it can pratically implement to their business. Keywords:  consumer decision journey, service marketing, third wave coffee